Bladder catheter dislodgement as a complication following placement of a subcutaneous ureteral bypass device. Issue 3 (7th September 2017) - Pilot, Mariette; Broome, Cameron; Hammond, Gawain; Ward, Patricia M; McLauchlan, Gerard
Abstract : A seven‐year‐old female, neutered, domestic short‐haired cat was presented with right‐sided hydroureter and hydronephrosis secondary to ureterolithiasis. A subcutaneous ureteral bypass (SUB) device was placed via mid‐line coeliotomy using fluoroscopic assistance. On routine examination 25 months after placement (three months after previous evaluation), urine could not be aspirated from the SUB port, and patency of the cystostomy catheter could not be confirmed under ultrasonographic flushing. Radiographs were performed and showed dislodgement and migration of the bladder catheter from the polyethylene terephthalate ('Dacron', Norfolk Vet Products, Skokie, Illinois, USA) cuff. No free abdominal fluid was present, and renal parameters and electrolytes were within normal limits. Fluoroscopic evaluation of the SUB device showed the native ureter was patent. Revision surgery was performed without complication. This complication has not been previously reported with the SUB device.